Cervical vertebral fusion with anterior meningocele. Issue 2 (April 2015) - Gallagher, Mathew J; Chavredakis, Emmanuel; Carter, David; Bhojak, Manesh; Jenkinson, Michael D; Clark, Simon R
We present the first described case of cervical vertebral fusion associated with anterior meningocele and syringomyelia. A 45-year-old woman presented with minor trauma, and plain cervical spine radiographs highlighted a congenital deformity of the cervical vertebral bodies. She had a normal neurological examination; however, further imaging revealed a meningocele and syringomyelia. This case highlights the importance of thorough imaging investigation when presented with a congenital deformity in order to detect and prevent development of degenerative spinal cord pathologies.